2002
DOI: 10.1046/j.1442-2042.2002.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of 18F‐fluorodeoxyglucose positron emission tomography (FDG‐PET) for detection of renal cell carcinoma and immunohistochemical glucose transporter 1 (GLUT‐1) expression in the cancer

Abstract: Objective: Positron emission tomography (PET) is now primarily used in oncological indication owing to the successful application of fluorine-18 fluorodeoxyglucose (FDG) in an increasing number of clinical indications. Glucose transporter 1 (GLUT-1) is recognized as a major early marker of cellular malignant transformation. The aims of this study were to assess whether FDG-PET is a useful diagnostic tool for renal cell carcinoma and to compare the pathologic characteristics. Methods: Nineteen consecutive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 7 publications
3
61
1
1
Order By: Relevance
“…The reported sensitivities and specificities of 18F-FDG-PET in subsequent studies have generally been suboptimal in comparison to diagnostic CT or MRI, with sensitivities ranging from 40%-94% and specificities ranging from 0%-100% (Kocher et al, 1994;Goldberg et al, 1997;Bachor et al, 1996;Montravers et al, 2000;Ramdave et al, 2001;Miyakita et al, 2002;Aide et al, 2003;Kang et al, 2004;Ak and Can, 2005;Kumar et al, 2005;Martinez et al, 2007). The low sensitivity of 18F-FDG- PET in some reports has been attributed to FDG excretion through the kidneys and collecting systems, decreasing contrast between renal lesions and normal tissues, as well as due to significant variability of 18F-FDG uptake that may be related to variable expression of GLUT-1 glucose transporters, tumor grade, presence of central necrosis, and/or lack of accessibility of 18F-FDG (Bachor et al, 1996;Miyauchi et al, 1996;Montravers et al, 2000;Miyakita et al, 2002;Aide et al, 2003). As we did not evaluate benign and malignant renal masses other than clear cell type, we did not calculate the specificity of 18F-FDG-PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…The reported sensitivities and specificities of 18F-FDG-PET in subsequent studies have generally been suboptimal in comparison to diagnostic CT or MRI, with sensitivities ranging from 40%-94% and specificities ranging from 0%-100% (Kocher et al, 1994;Goldberg et al, 1997;Bachor et al, 1996;Montravers et al, 2000;Ramdave et al, 2001;Miyakita et al, 2002;Aide et al, 2003;Kang et al, 2004;Ak and Can, 2005;Kumar et al, 2005;Martinez et al, 2007). The low sensitivity of 18F-FDG- PET in some reports has been attributed to FDG excretion through the kidneys and collecting systems, decreasing contrast between renal lesions and normal tissues, as well as due to significant variability of 18F-FDG uptake that may be related to variable expression of GLUT-1 glucose transporters, tumor grade, presence of central necrosis, and/or lack of accessibility of 18F-FDG (Bachor et al, 1996;Miyauchi et al, 1996;Montravers et al, 2000;Miyakita et al, 2002;Aide et al, 2003). As we did not evaluate benign and malignant renal masses other than clear cell type, we did not calculate the specificity of 18F-FDG-PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…FDG PET has been attempted in the evaluation of tumor response to molecular targeting therapy including sunitinib [3,4]. However, FDG PET has some limitations in evaluating the early effects of cancer therapy, such as its high uptake in tumors early after therapy and its relatively low accumulation in RCC tumor tissue [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…GLUT-1 is overexpressed in VHL-mutated mice and the GLUT-1 promoter region has an HRE (Ebert et al, 1995;Park et al, 2007;Lidgren et al, 2008). While the basal level of expression of GLUT-1 in normal PTEC is a subject of debate (Nagase et al, 1995;Ozcan et al, 2007), the overexpression of GLUT-1 in RCC has been demonstrated by many studies (Nagase et al, 1995;Miyakita et al, 2002;Ozcan et al, 2007;Suganuma et al, 2007;Lidgren et al, 2008;Singer et al, 2011). All of these studies concluded that GLUT-1 is over-expressed markedly in clear cell RCC compared with other RCC subtypes, confirming the link between VHL aberration and the subsequent HIF up-regulation.…”
Section: Glucose Transporter-1mentioning
confidence: 99%